2020
DOI: 10.30742/jv.v10i0.41
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Artikel: Potensi Plasma Non Termal Sebagai Kandidat Terapi Mastitis Subklinis

Abstract: Subclinical mastitis is the occurrence of inflammation in the parenchymal tissue of mammaryglands due to bacterial contamination that does not show clinical symptoms lead to impacted oneconomic losses. The highest incidence of subclinical mastitis is the presence of Staphylococcusaureus bacteria contamination. Subclinical mastitis in Indonesia is reported to reduce milk productionby up to 53.5%. Pathogenesis of Staphylococcus aureus occurs in the presence of biofilm formation asbacterial immune system to prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…At the same time, O3 can interfere with cellular respiration. Protein molecules that make up bacterial cell membranes are known to be susceptible to oxidation processes, so that non-thermal plasma treatment on bacteria can cause erosion that results in the rupture of bacterial cell walls (Akter et al, 2020;Amalda et al, 2020;Fallon et al, 2020;Feng & Wang, 2020;Gaur et al, 2021). These results prove that ROS reduction while using a nitrogen gas source causes no significant reduction in the number of colonies.…”
Section: Effectiveness Of Inactivation Of E Coli Bacteria As a Result...mentioning
confidence: 91%
See 3 more Smart Citations
“…At the same time, O3 can interfere with cellular respiration. Protein molecules that make up bacterial cell membranes are known to be susceptible to oxidation processes, so that non-thermal plasma treatment on bacteria can cause erosion that results in the rupture of bacterial cell walls (Akter et al, 2020;Amalda et al, 2020;Fallon et al, 2020;Feng & Wang, 2020;Gaur et al, 2021). These results prove that ROS reduction while using a nitrogen gas source causes no significant reduction in the number of colonies.…”
Section: Effectiveness Of Inactivation Of E Coli Bacteria As a Result...mentioning
confidence: 91%
“…This is also supported by research from (Belgacem et al 2017) (Belgacem et al, 2017) and (Carré et al, 2018), which showed that the highest bacterial inactivation rate was obtained using oxygen as a plasma reactor gas. So oxygen becomes raw material in forming reactive oxygen species (ROS), which are effective agents of inactivating bacteria in non-thermal plasma (Amalda et al, 2020). When accumulated, ROS cause oxidative stress resulting in protein, DNA, and lipid damage, and even cell death (Akter et al, 2020;Feng & Wang, 2020).…”
Section: Effectiveness Of Inactivation Of E Coli Bacteria As a Result...mentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism and level of decontamination capability vary depending on the length of treatment time, the distance of treatment, the amount of voltage used, and the source of the gas used. All play a role in how e ective non-thermal plasma is at decontaminating bacteria (Amalda et al, 2020) . In research on bacterial inactivation using SDBD non-thermal plasma treatment, variations in treatment time and treatment distances were used.…”
Section: E Ect Of Treatment Time and Distance Of Sbdb Nonthermal Plas...mentioning
confidence: 99%